Media Sosial TikTok sebagai Agen Sosialisasi dalam Membentuk Konsep Diri - Wilis Wening Rumasmoro; Yosafat Hermawan Trinugraha; Septina Galih Pudyastuti (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
Social media TikTok has become a media that is quite popular among teenagers. The massive use of social media TikTok among teenagers makes it a powerful socialization agent in forming self-concept. This research uses descriptive qualitative methods to determine the self-concept of teenagers using TikTok social media. The research was carried out using in-depth interviews and observations of purposive sampling of informants involving 5 teenage users of the social media TikTok. The primary data used in this research is the results of interviews with informants, while the secondary data is in the form of books and relevant literature studies. The data obtained was then analyzed using the Looking Glass Self (Cooley) theory. The findings obtained in this research indicate that a positive view of the video content or comments uploaded will form a positive self-concept in teenagers who use the social media TikTok. On the other hand, having a negative view of the video content or comments uploaded will form a negative self-concept in teenagers who use the social media TikTok. This self-concept develops based on the reflections of teenage TikTok social media users on other people's views on uploaded video content or comments.